Multispecies relations shape bird-feeding practices - Aivelo, Tuomas; Aulio, Mikko; Enström, Johanna; Deshpande, Purabi Pramod; Haukka, Anna; Lähdesmäki, Heta; Rönkä, Katja Helena; Santangeli, Andrea; Väkkärä, Virpi Anneli; Lehikoinen, Aleksi; Thorogood, Rose; Kervinen, Anttoni (United Kingdom, 2025)
While humans often feed birds in their backyards, there is a growing awareness that this has positive and negative effects on local biodiversity. Whether the observed species assemblage shapes human activities has, however, rarely been investigated. We analyzed 15,088 open-ended answers from 9473 Finnish respondents about why they have increased or reduced feeding birds. They mentioned 58 avian and non-avian species linked to changed practices. The main reasons for change were (1) respondent’s relation to nonhuman species, (2) respondent’s relation to other humans, and (3) relations between nonhuman species. Most taxa and reasons could lead to both increase or decrease in feeding, although the direction was context-dependent. We suggest that bird-feeding is an interactive process where the species community strongly affects feeding practices, which in turn can affect community composition. Recognizing this process is crucial for understanding the effects of bird-feeding on both humans and nature and providing more nuanced guidance.